Optimum medium components for biosurfactant production by Klebsiella pneumoniae WMF02 utilizing sludge palm oil as a substrate - Jamal, Parveen; Wan Nawawi, Wan Mohd Fazli; Alam, Md. Zahangir (INSI Publications, 2012)
In the present study, optimizing critical nutritional constituents was attempted as a primary strategy to improve biosurfactant production from Klebsiella pneumoniae WMF02 in liquid state fermentation utilizing sludge palm oil as a substrate. One-factor-at-a-time (OFAT) optimization was employed to evaluate the effects of sludge palm oil (SPO), sucrose, MgSO4, FeSO4, NaNO3 and K2HPO4 on surface tension reductivity. Sucrose was selected as a co-substrate over glucose in production media. The optimal levels of the aforementioned variables were (g/l) sucrose 5.0, MgSO4 0.4, FeSO4 0.3, NaNO3 2.0, and K2HPO4 4.0, with SPO concentration of 4% (v/v). The optimized medium shows surface tension reduction from 36.2 mN/m (non-optimized medium) to 25.70 mN/m. Preliminary biosurfactant identification indicated that the biosurfactant produced was phospholipids in nature.